Staging gallbladder cancer with lymphadenectomy: the practical application of new AHPBA and AJCC guidelines. Issue 11 (November 2019) - Leigh, Natasha L.; Solomon, Daniel; Feingold, Daniela; Hiotis, Spiros P.; Labow, Daniel M.; Magge, Deepa R.; Sarpel, Umut; Golas, Benjamin J.
Abstract: Background: Current guidelines recommend harvesting a total lymph node count (TLNC) ≥6 from portal lymphadenectomy in ≥pT1b gallbladder cancers (GBC) for accurate staging and prognostication. This study aimed to determine nodal yields from portal lymphadenectomy and identify measures to maximize TLNC. Methods: We retrospectively reviewed all ≥pT1b GBC which underwent resection with curative intent including portal lymphadenectomy at our specialized HPB center from 2007 to 2017. We compared outcomes of TLNC < 6 and TLNC ≥ 6 cohorts and determined factors predictive of TLNC. Results: Of 92 patients, 20% had a TLNC ≥ 6 (IQR 7–11) and 9% had no nodes found on pathology. Malignant lymphadenopathy was twice as common in TLNC ≥ 6 as TLNC < 6 (p = 0.003) most frequently from portal, cystic and pericholedochal stations. On logistic regression analysis, concomitant liver resection was an independent predictor of higher TLNC [4b/5 wedge resection (OR 0.166, CI 0.057–0.486, p = 0.001) extended hepatectomy (OR 0.065, CI 0.012–0.340, p = 0.001)]; biliary resection and en bloc adjacent organ resection were not. Conclusion: At our center, prior to current guidelines, a TLNC≥6 was not met in 80% undergoing portal lymphadenectomy for ≥ pT1b GBC. To increase nodal yield, future guidelines should consider including additional lymph node stations and incorporation of frozen section analysis.